(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract: There have been various types of research and literature written to describe the impact of COVID-19 on business and the supply chain. However, data regarding the impact of the COVID-19 situation especially on project management has been very limited. The paper will attempt to reduce the literature gap by discussing the impact of COVID-19 on project management. Where we relied on a conceptual framework that uses COVID-19 as the independent variable and project management as the dependent variable, we used theoretical empirical research methods we collected data from a variety of sources, including online government documents and articles…etc. Through this, we concluded that the impact of COVID-19 significantly on the project management was negative, which caused the interruption of operations and unavailability of supplies and caused the restructuring. However, it has taught project management teams and other stakeholders some significant lessons including the importance of planning, flexibility, and collaboration. keywords: covid-19,Project management, strategy ملخص: كانت هناك أنواع مختلفة من الأبحاث والأدبيات المكتوبة لوصف تأثير COVID-19 على الأعمال التجارية وسلسلة التوريد. ومع ذلك ، فإن البيانات المتعلقة بتأثير حالة COVID-19 خاصة على إدارة المشاريع كانت محدودة للغاية. لذلك حاولنا من خلال هذه الورقة تقليل فجوة الأدبيات من خلال مناقشة تأثير COVID-19 على إدارة المشاريع. حيث اعتمدنا على إطار مفاهيمي يستخدم COVID-19 كمتغير مستقل وإدارة المشاريع كمتغير تابع ، اتبعنا في بحثنا هذا طرق البحث التجريبية النظرية حيث قمنا بجمع المعلومات من مصادر متنوعة، بما في ذلك الوثائق الحكومية عبر الإنترنت والمقالات ... إلخ. بعد معالجة البيانات تخلصنا إلى أن تأثير كوفيد -19 على إدارة المشاريع كان سلبياً بشكل كبير، حيث تسبب في توقف العمليات وعدم توفر الإمدادات وتسبب في إعادة هيكلة العديد من المشاريع والمنظمات. ومع ذلك، فقد قام بتعليم فريق ادارة المشاريع واصحاب المصالح اهمية التخطيط والمرونة والتعاون. كلمات دالة: إدارة المشاريع، جائحة كورونا، الاستراتيجية